A review on the role of miRNA-324 in various diseases - Kadkhoda, Sepideh; Hussen, Bashdar Mahmud; Eslami, Solat; Ghafouri-Fard, Soudeh (Frontiers in Genetics, 2022)
Recent studies have revealed important functions of several microRNAs (miRNAs) in the pathogenesis of human diseases. miR-324 is an example of miRNAs with crucial impacts on the pathogenesis of a wide range of disorders. Gene ontology studies have indicated possible role of miR-324 in responses of cells to the leukemia inhibitory factor, long-term synaptic potentiation, positive regulation of cytokines production and sensory perception of sound. In human, miR-324 is encoded by MIR324 gene which resides on chromosome 17p13.1. In the current manuscript, we provide a concise review of the role of miR-324 in the pathogenesis of cancers as well as non-cancerous conditions such as aneurysmal subarachnoid hemorrhage, diabetic nephropathy, epilepsy, pulmonary/renal fibrosis, ischemic stroke and ischemia reperfusion injuries. Moreover, we summarize the role of this miRNA as a prognostic marker for malignant disorders.